Detour Pebbling Number on Some Commutative Ring Graphs - Lourdusamy, A.; Iammal, S. Kither; Dhivviyanandam, I. (Communications in Mathematics and Applications, 2023)
The detour pebbling number of a graph \(G\) is the least positive integer \(f^{*}(G)\) such that these pebbles are placed on the vertices of \(G\), we can move a pebble to a target vertex by a sequence of pebbling moves each move taking two pebbles off a vertex and placing one of the pebbles on an adjacent vertex using detour path. In this paper, we compute the detour pebbling number for the commutative ring of zero-divisor graphs, sum and the product of zero divisor graphs.